Fala - Klimo, Kate (Klimo, Kate. Dog diaries., 2016)
Fala, the Scottish terrier, President Franklin Delano Roosevelt's pet, shares his story with readers, from his puppyhood spent chasing squirrels through his adulthood spent chasing dignitaries around the world with FDR.